LEVERAGING INNOVATION AND CRM: A STRATEGIC ANALYSIS OF SME PERFORMANCE IN PLATEAU STATE - Amadi, James Ndubuisi; Olubunmi, Esther Kemi (Research Journal of Economics and Sustainable Development, 2024)
Small and medium-sized enterprises (SMEs) contribute significantly to the economic development of both emerging and established economies by providing up to 40% of the gross domestic product and 60% of total employment opportunities in developing countries. However, SMEs face some difficulties such as inadequate funding, poor planning, and poor management practices, which affect their performance. This research analyzes the impact of customer relationship management (CRM) and innovation capability on the performance of SMEs in Nigeria's Plateau state. The study uses the relationship marketing theory and dynamic capabilities theory to support its analysis and assesses the performance of SMEs from the perspectives of finance, customers, internal operations, and staff learning and development. A mixed-method approach was used in this study, which includes a survey and in-depth interviews with SME owners and managers. The findings of this research show that CRM, marketing innovation, process innovation and product innovation are critical to the performance of SMEs. The study recommends that SMEs should adopt innovative strategies to improve customer retention and boost productivity, which will enhance their performance.